PARTISIPASI MASYARAKAT DALAM PELAYANAN PUBLIK DI KANTOR PERTANAHAN KABUPATEN BOYOLALI MELALUI BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK - SUPRIADI, SUPRIADI (Dinamika Hukum, 2018)
The purpose of this study is to: 1) examines the public participation in the implementation of public services at the national land Agency Boyolali Regency based on Law No. 25 of the year 2009. 2) examines the obstacles that occur in the implementation of public services at the national land Agency Boyolali Regency based on Law No. 25 of the year 2009. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) community participation in the implementation of public services at the national land Agency Boyolali Regency based on Law No. 25-year 2009 carried out by providing input and advice on service quality management certificates, namely by way of writing the critique and suggestions for inclusion into the suggestion box and through media research in the form of filling questionnaire. 2) barriers that occur in the implementation of public services at the national land Agency Boyolali Regency based on Law No. 25 of the year 2009, namely in the form of non technical barriers and technical barriers. Non technical barriers, namely: 1) still has that seal pathok SPPT is evidence and the rights of land ownership. 2) still views the community it's hard to be a land registry project participants through Prona (the National Agrarian Project). 3) there is still the assumption that need not bother to register land. Technical barriers in the form of: 1) Occurs the debate between landowners concerned with adjacent landowners regarding land boundaries are designated by each party. 2 do not landowners) were in place when the measurement was held. 3) evidence of ownership is not complete. Keywords: Public Participation, Public Service.